Public–Private Partnerships As A Policy Tool For Local Infrastructure Development - Okotie William (Universitas Medan Area, 2026)
PPP (Public Private Partnerships) is also a growing trend in policy as a way of solution to infrastructure deficits at the local government in Nigeria. This paper examines the contribution of PPPs to infrastructure growth in localities, with particular reference to roads, water supply, sanitation, and waste management. The study adopts a qualitative desk-based research design, drawing on secondary data using academic literature, policy documents, government reports and case studies chosen. The theory to be applied in this analysis is the New Public Management theory, which focuses on efficiency, accountability and involvement of the private sector in the delivery of services by the government. Findings indicate that the PPPs can mobilise private capital, technical expertise, and managerial efficiency in areas where the amount of resources supplied by the government is insufficient. Nonetheless, there are still considerable challenges such as weak regulatory frameworks, institutional capacity of the local governments, bad contract management, corruption and poor community engagement. These limitations tend to compromise the project performance and sustainability. The study concludes that PPPs can only be policy workable when it is backed with effective governance systems, transparency and an increase of the local government institutional capacity.